2011
DOI: 10.5194/nhess-11-2047-2011
|View full text |Cite
|
Sign up to set email alerts
|

The application of numerical debris flow modelling for the generation of physical vulnerability curves

Abstract: Abstract. For a quantitative assessment of debris flow risk, it is essential to consider not only the hazardous process itself but also to perform an analysis of its consequences. This should include the estimation of the expected monetary losses as the product of the hazard with a given magnitude and the vulnerability of the elements exposed. A quantifiable integrated approach of both hazard and vulnerability is becoming a required practice in risk reduction management. This study aims at developing physical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
117
1
6

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(126 citation statements)
references
References 34 publications
2
117
1
6
Order By: Relevance
“…As far as debris flow is concerned, the first approaches for physical vulnerability assessment were qualitative (Fell and Hartford, 1997;Liu and Lei, 2003;Romang, 2004), including in some cases vulnerability matrices (Leone et al, 1995(Leone et al, , 1996Sterlacchini et al, 2007;Zanchetta et al, 2004) showing a descriptive relationship between the damage and intensity of the flow. However, recently the number of vulnerability curves for debris flows has considerably increased and several studies may be found in the literature Papathoma-Köhle et al, 2012;Quan Luna et al, 2011;Totschnig and Fuchs, 2013;Totschnig et al, 2011). Each vulnerability curve has been developed for a specific area, is based on a particular catastrophic event and expresses the intensity of the process in various ways.…”
Section: Methods For Assessing Physical Vulnerabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…As far as debris flow is concerned, the first approaches for physical vulnerability assessment were qualitative (Fell and Hartford, 1997;Liu and Lei, 2003;Romang, 2004), including in some cases vulnerability matrices (Leone et al, 1995(Leone et al, , 1996Sterlacchini et al, 2007;Zanchetta et al, 2004) showing a descriptive relationship between the damage and intensity of the flow. However, recently the number of vulnerability curves for debris flows has considerably increased and several studies may be found in the literature Papathoma-Köhle et al, 2012;Quan Luna et al, 2011;Totschnig and Fuchs, 2013;Totschnig et al, 2011). Each vulnerability curve has been developed for a specific area, is based on a particular catastrophic event and expresses the intensity of the process in various ways.…”
Section: Methods For Assessing Physical Vulnerabilitymentioning
confidence: 99%
“…13 buildings in Fuchs et al, 2007) or a larger number of buildings (1560 buildings in Lo et al, 2012). In some cases, due to lack of empirical data, information on the process had to be derived through modelling (Quan Luna et al, 2011;Rheinberger et al, 2013) that expressed the flow not only as debris height but also as velocity, viscosity or impact pressure. As far as the degree of loss is concerned, relevant information could be provided in some cases by the authorities.…”
Section: Methods For Assessing Physical Vulnerabilitymentioning
confidence: 99%
“…The relationship between impact intensity and degree of loss is commonly expressed in terms of a vulnerability curve or vulnerability function (Totschnig and Fuchs, 2013), although also semi-quantitative and qualitative methods exist (Totschnig and Fuchs, 2013;Fuchs et al, 2007;Jakob et al, 2012;Kappes et al, 2012). The intensity criteria of torrent (steep stream) processes, encompassing clear water, hyperconcentrated and debris flows, has been considered in terms of impact forces Quan Luna et al, 2011;Hu et al, 2012); deposit height (Mazzorana et al, 2012;Fuchs et al, , 2007Akbas et al, 2009;Totschnig et al, 2011;Lo et al, 2012;Papathoma-Köhle et al, 2012;Totschnig and Fuchs, 2013); kinematic viscosity (Quan Luna et al, 2011;Totschnig et al, 2011); flow depth (Jakob et al, 2013;Tsao et al, 2010;Totschnig and Fuchs, 2013); flow velocity times flow depth (Totschnig and Fuchs, 2013); and velocity squared times flow depth (Jakob et al, 2012). Different types of elements at risk will show different levels of damage given the same intensity of hazard (Jha et al, 2012;Albano et al, 2014;Liu et al, 2014), therefore vulnerability curves are developed for a particular type of exposed element (such as construction type, building dimensions or road access conditions).…”
Section: Conceptualisation Of Vulnerabilitymentioning
confidence: 99%
“…residential buildings, see Papathoma-Köhle et al, 2011, for an overview). In particular, vulnerability functions for buildings impacted by debris flows (Fuchs et al, 2007b;Akbas et al, 2009;Quan Luna et al, 2011) and fluvial sediment transport (Totschnig et al, 2011) are limited. In most of these studies vulnerability was measured using an economic approach and derived from the quotient between the loss and the individual reinstatement value for each element at risk considered.…”
Section: Vulnerability Of Endangered Elementsmentioning
confidence: 99%